PENGEMBANGAN COMPUTER BASED TEST (CBT) BERBASIS WEB SEBAGAI ALTERNATIF TEKNIK PENILAIAN HASIL BELAJAR DI SMP ISLAM AL AMIN - Hariyani, Sari Ika; Wahyuningsih, Anik Sri; Krisnayadi, Yogie (Jurnal Ilmiah Sistem Informasi, 2024)
Effective assessment of learning outcomes is a crucial component of the educational process. In this study, a **Computer-Based Test (CBT)** system was developed as an alternative method for assessing learning outcomes at **SMP Islam Al Amin**, Cikarang Utara. The study aims to improve the efficiency, accuracy, and objectivity of assessments while facilitating the use of technology in learning. The research methodology involved designing and developing a computer-based test tailored to the school's curriculum. The results showed that the CBT system successfully enhanced the efficiency of assessments, provided rapid feedback, and improved the technological skills of both students and teachers. The implementation of this system proved to be an effective alternative compared to traditional assessment methods.